DIVERSI DALAM PERLINDUNGAN HUKUM ANAK YANG BERMASALAH HUKUM DALAM SISTEM PERADILAN PIDANA ANAK - Unbanunaek Mimi Jimmy Pello Karolus Kopong Medan (Masalah-Masalah Hukum, 2014)
Diversion is a new method in the resolution of criminal offenses committed by children. aspect of this research is how the legal protection of children in conflict with the law through the concept of diversion in terms of legislation juvenile justice system, what distinguishes the concept of diversion in Indonesia and other countries an how the juvenile system that is ideal in order for the legal protection of children the conflict with the law. in addition, this study also analyzed the cases of children in conflict with the law and associated with settlement through diversion